KANDUNGAN FRAKSI SERAT RUMPUT ALAM PADA KETINGGIAN LOKASI YANG BERBEDA DI KABUPATEN TIMOR TENGAH SELATAN - Vivin Elmiyati Se'u; Yelly Magdalena Mulik (Partner, 2020)
This study aims at determining the content of natural grass fiber fraction at different altitudes. The method used was a survey method and each location had 10 plots by making random plots in taking the samples for laboratory analysis and descriptive analysis. The parameter measured was the fiber fraction. The results showed that the highest content of NDF fiber fraction was in Noebeba District while the highest content of ADF, Cellulose and Lignin was in South Amanuban District, while the lowest content of NDF, ADF, Cellulose, lignin was in North Mollo District and the lowest hemicellulose content was in South Amanuban District.